2018
DOI: 10.1139/apnm-2017-0788
|View full text |Cite
|
Sign up to set email alerts
|

Kolaviron attenuates diclofenac-induced nephrotoxicity in male Wistar rats

Abstract: The beneficial effects of kolaviron, a natural biflavonoid from the seeds of Garcinia kola, have been attributed to its antioxidant and anti-inflammatory activities. This study was designed to investigate the renoprotective effect of kolaviron in rat model of diclofenac (DFC)-induced acute renal failure. Thirty-five male Wistar rats were divided into 7 groups of 5 rats each as follows: a control group that received propylene glycol orally and treatment groups that received DFC, DFC recovery, DFC followed by ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…The present study illustrated significant nephrotoxicity which induced by diclofenac through elevation of blood urea and serum creatinine compared to the control in the experimental rats as supported by Alabi et al [18].…”
Section: Discussionsupporting
confidence: 81%
“…The present study illustrated significant nephrotoxicity which induced by diclofenac through elevation of blood urea and serum creatinine compared to the control in the experimental rats as supported by Alabi et al [18].…”
Section: Discussionsupporting
confidence: 81%
“…These results are in accordance with the previous researches. 17,26,37 Ateşşahín et al 38 and Abdel-Daim et al 39 have confirmed ROS over generation in kidney and liver tissues as a result of increase in MDA concentrations in the renal and hepatic tissues, which resulted to necrosis and back leak of liver enzymes and kidney function makers into circulation. Interestingly, the protective effect observed for KV in both the kidneys and liver of rats treated with DF indicated that KV may be involved in the elimination of ROS or other reactive bye products generated by DF toxic metabolites in both the kidney and liver tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Kolaviron was isolated from Garcinia kola according to the previous methods. 24,26 The KV obtained was dissolved in propylene glycol (0.2 mL/administration) and given to rat according to the designed dosage.…”
Section: Extraction Of Kvmentioning
confidence: 99%
“…The present study demonstrated noteworthy AKI that was induced by diclofenac through the rise of blood urea and serum creatinine compared with control in the experimental rats as maintained by a previous study that showed diclofenac leads to significant renal tubular necrosis and AKI. [16]…”
Section: Discussionmentioning
confidence: 99%